Application of Taiwan’s Human Rights-Themed Cultural Assets and Spatial Information - Shuhui Lin (Complexity)
Cultural assets preserve the traces of people’s life history around the world. With an understanding of the historical context and meaning of cultural assets, people would cherish their value and then adopt appropriate cultural resource preservation strategies. Human rights as the universal value refer to the inalienable and basic rights of human beings. This article uses the National Cultural Assets Network to query Taiwan’s human rights-themed cultural assets, and I apply the spatial information technology of the DocuSky digital humanities academic research platform to draw the maps with GIS and visualization tools. Also, I apply spatial information to the academic research of human rights-themed cultural assets, aiming to deepen local cultural identity and unveiling that human studies influence spatial practice. Tourism is an important experience economy. Based on the value of Taiwan’s human rights-themed cultural assets, I plan to guide the human rights journey in Taipei to share Taiwan’s experience of happiness with the world, as well.